Bogoyavlenskaya story - Nadezhda Pospelova; Valentina Dedyk; Anatoly Sorokin (Alexander King, 2013)
Anna Petrovna reads a story that she published in the newspaper. She starts by just using the text as a memory aid, but by the middle, she is reading fairly closely. This track has some interruptions and Russian passages (complaints) edited out. Palana-TASCAM130113_cInt.wav provides ambient audio. Ambient audio for lapel mic track. This file includes bits deleted from Ext. Ends with a bit of commentary on style in Russian. Born and raised in Lesnaya. Mother from Khailino, father from Lesnaya. Works in Institute for Advanced Teacher Training, Palana. She was born in a yaranga on the tundra. Also fluent (listening, reading, some writing/speaking) in English and Japanese. Alutor level is elementary.